The Effect of Kinesiotaping and Nerve Mobilization on Reduction of Doms - Suriani Sari; Zusyah Porja Daryanto (INSPIREE: Indonesian Sport Innovation Review, 2023)
The purpose of the study. This research aims to determine the effectiveness of giving ice massage  after training in reducing the occurrence of DOMS. Method. The research design  used was the Post Test Only With Control Group Design research method, the  sample size was 20 students. The sample was divided into 2 groups, group I was  the treatment group (kinesiotaping and nerve mobilization) and group 2 was the  control group (without kinesiotaping and nerve mobilization). Subjects performed  maximal contractions and exceeded the training load. Subjects performed 75  contractions and divided into 3 training sets. Each set of 25 contractions with a load  of 18 kg. After training, the treatment group was given kinesiotaping and nerve  mobilization, kinesiotaping and nerve mobilization were given after 30 minutes of  training in the treatment group, then the control group was not given kinesiotaping  and nerve mobilization. DOMS measurements were carried out using the talaq  scale, where measurements were carried out after kinesiotaping and nerve  mobilization were given and without kinesiotaping and nerve mobilization. Result. For the  non-kinesiotaping and nerve mobilization variables, the probability obtained was p  0.010 < 0.05. The difference between the treatment group and the control group  using the Mann-Whitney test obtained a probability of 0.026 < 0.05. Conclusion.  By looking at the results of the data obtained, it can be concluded that providing  kinesiotaping and nerve mobilization as quickly as possible can reduce the risk of  DOMS, whereas without providing kinesiotaping and nerve mobilization cannot  reduce the risk of DOMS. To avoid wider damage from the effects of overloaded  training, giving ice massage early will help reduce the risk of DOMS.